Personalisation of Intelligent Homecare Services Adapted to Children with Motor Impairments - Valero, Miguel Ángel; Lindén, Maria; Velasco, Juan Ramón; Björkman, Mats (Ubiquitous Computing and Ambient Intelligence. Personalisation and User Adapted Services, 2014)
Ambient Intelligence could support innovative application domains like motor impairments’ detection at the home environment. This research aims to prevent neurodevelopmental disorders through the natural interaction of the children with embedded intelligence daily life objects, like home furniture and toys. Designed system uses an interoperable platform to provide two intelligent interrelated home healthcare services: monitoring of children’s abilities and completion of early stimulation activities. A set of sensors, which are embedded within the rooms, toys and furniture, allows private data gathering about the child’s interaction with the environment. This information feeds a reasoning subsystem, which encloses an ontology of neurodevelopment items, and adapts the service to the age and acquisition of expected abilities. Next, the platform proposes customized stimulation services by taking advantage of the existing facilities at the child’s environment. The result integrates Embedded Sensor Systems for Health at Mälardalen University with UPM Smart Home, for adapted services delivery.